Genetic, biochemical, and environmental factors associated with pregnancy outcomes in newborns from the Czech Republic - Rossner, Pavel; Tabashidze, Nana; Dostal, Miroslav; Novakova, Zuzana; Chvatalova, Irena; Spatova, Milada; Sram, Radim J (Environmental health perspectives, 2011)
BACKGROUND: Oxidative damage to placental DNA can result in negative pregnancy outcomes, including intrauterine growth restriction (IUGR) and low birth weight (LBW). OBJECTIVE: We investigated associations between the levels of 8-oxo-7,8-dihydro-2´-deoxyguanosine (8-oxodG), a marker of oxidative DNA damage, in placental DNA, exposure to air pollutants during pregnancy, genetic polymorphisms in 94 selected genes, and pregnancy outcomes. METHODS: We studied 891 newborns who were IUGR- or LBW-affected or normal weight and were born between 1994 and 1999 in the Czech Republic in two districts with different levels of air pollution. RESULTS: We found nonsignificantly elevated 8-oxodG levels in the IUGR-affected group compared with the non-IUGR group (p = 0.055). Similarly, slightly elevated 8-oxodG levels were found in the LBW-affected group compared with the non-LBW group (p < 0.050). In univariate analyses, we identified single nucleotide polymorphisms associated with 8-oxodG levels, IUGR, and LBW. Exposure to particulate matter < 2.5 µm was associated with increased 8-oxodG levels in placental DNA and LBW. However, multivariate-adjusted logistic regression revealed that above-median 8-oxodG levels were the only factor significantly associated with IUGR [OR = 1.56; 95% confidence interval (CI), 1.07-2.37; p = 0.022]. Above-median levels of 8-oxodG were associated with LBW (OR = 1.88; 95% CI, 1.15-3.06; p = 0.011). Other variables associated with LBW included sex and gestational age of the newborn, maternal smoking, and haplotypes in the promoter region of the gene encoding mannose-binding lectin 2 (MBL2). The role of air pollutants in the risk of adverse pregnancy outcomes seemed to be less important. CONCLUSIONS: Levels of 8-oxodG in placental DNA were associated with the risk of IUGR as well as LBW. Newborn's sex, gestational age, maternal smoking, and genetic polymorphisms in the promoter region of the MBL2 gene were associated with LBW incidence.
Keywords: 8-Hydroxy-2'-Deoxyguanosine; Particulate Matter; pevné částice; růstová retardace plodu; Pregnancy; těhotenství; výsledek těhotenství; Case-Control Studies; deoxyguanosin; novorozenec; Pregnancy Outcome; lidé; Fetal Growth Retardation; ženské pohlaví; studie případů a kontrol; Humans; Infant, Newborn; Infant, Low Birth Weight; DNA; Female; 8-hydroxy-2'-deoxyguanosin; Deoxyguanosine; novorozenec s nízkou porodní hmotností